1968
DOI: 10.1107/s0567740868002657
|View full text |Cite
|
Sign up to set email alerts
|

Disorder in crystals of the dithienyls and β-thiophenic acid

Abstract: The crystal structures of the three isomeric dithienyls C8H652 have been determined by three-dimensional X-ray methods. In all cases the molecules in the solid are planar. Crystals of 2,2'-dithienyl appeared to decompose during the X-ray exposures; those of 2,3"-dithienyl and 3,3'-dithienyl show disorder. Disorder as found in 3,3'-dithienyl may also be assumed for fl-thiophenic acid. Within the rather large experimental errors the bond lengths and angles in the thiophene rings of the dithienyls are equal to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
1

Year Published

1977
1977
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(72 citation statements)
references
References 3 publications
5
65
1
1
Order By: Relevance
“…Crystal data MolEN programs (Fair, 1990) In contrast to the other reported structure determinations (Visser et al, 1968;Pelletier & Brisse, 1994), we found no crystal decay at all during data collection. The rings are slightly disordered, with an 0.85 occupancy as shown in Fig.…”
Section: Methodscontrasting
confidence: 54%
See 2 more Smart Citations
“…Crystal data MolEN programs (Fair, 1990) In contrast to the other reported structure determinations (Visser et al, 1968;Pelletier & Brisse, 1994), we found no crystal decay at all during data collection. The rings are slightly disordered, with an 0.85 occupancy as shown in Fig.…”
Section: Methodscontrasting
confidence: 54%
“…Although the structures of other bithienyls have been established and a number of oligothiophenes have also been studied (e.g. Jayasuriya, Kagan, Huang & Teo, 1988;Visser, Heeres, Wolters & Vos, 1968), a good quality structure of bithiophene, (I), itself had not been reported. An early determination (Visser et al, 1968) was of low accuracy; the crystals, obtained by recrystallization from toluene, decomposed during data collection.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it appears that the trans conformer of R2, albeit twisted around the inter-ring bond, is lower in energy. 32, [38][39][40] Note that MOPAC and MNDO93,PM3 incorrectly predict the a Gaussian 92 code was used for all ab initio calculations. For one of them, 6-31G(d), a polarization function (d-orbital) was added for C and S atoms.…”
Section: Resultsmentioning
confidence: 99%
“…I1 enest de m~me pour les angles Fe--C-O dont la moyenne est de 172,1 (0,8) °, valeur relativement faible, sans doute li6e fi la mauvaise precision. Les cycles thioph6ne non complex6s pr6sentent des distanees et angles ~ peu pr6s normaux, mais 1~ aussi la faible pr6cision emp~che une discussion plus pouss6e et une comparaison avec les structures du bithi6nyl-2,2' (Visser et al, 1968) ou du thioph6ne (Bak, Christensen, Hansen-Nygaard & Rastrup-Andersen, 1961;Bonham & Momany, 1963). Les cycles thioph6ne libres peuvent &re eonsid6r~s comme plans dans la limite de pr6eision exp6rimentale.…”
Section: Description De La Structure Et Discussionunclassified